Molecular genetic analysis of the neurokinin B (TAC3) and neurokinin B receptor (TAC3) genes as candidates for pre-eclampsia - Carelse Tofa, Kashefa (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2004.